2015
DOI: 10.1159/000381838
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cytological Comparisons of Chromosomes 7el<sub>1</sub>, 7el<sub>2</sub>, 7E<sup>e</sup>, and 7E<sup>i</sup> Derived from <b><i>Thinopyrum</i></b>

Abstract: Thinopyrum chromosomes 7el1, 7el2, 7Ee, and 7Ei, homoeologous to group 7 chromosomes of common wheat (Triticum aestivum), were determined to have many useful agronomical traits for wheat improvement. To analyze the genetic relationships among the 4 Thinopyrum 7E chromosomes, the conserved orthologous set markers, genomic in situ hybridization (GISH), and meiotic chromosome pairing were used in this study. The unweighted pair-group method with arithmetical averages (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Previously, we mapped the Fhb7 to the distal end of the 7EL (based on recombination between 7E1 and 7E2 in a common wheat background) using a recombinant inbred line (RIL) population from a cross between an FHBsusceptible substitution line (7E1/7D) and an FHB-resistant substitution line (7E2/7D) (13,21). For further mapping of this gene, we developed a segregation population derived from BC 6 F 1 with the same cross, in which FHB resistance was tracked as monogenic trait for validation of phenotypes.…”
Section: Map-based Cloning Of the Fusarium Resistance Gene Fhb7mentioning
confidence: 99%
“…Previously, we mapped the Fhb7 to the distal end of the 7EL (based on recombination between 7E1 and 7E2 in a common wheat background) using a recombinant inbred line (RIL) population from a cross between an FHBsusceptible substitution line (7E1/7D) and an FHB-resistant substitution line (7E2/7D) (13,21). For further mapping of this gene, we developed a segregation population derived from BC 6 F 1 with the same cross, in which FHB resistance was tracked as monogenic trait for validation of phenotypes.…”
Section: Map-based Cloning Of the Fusarium Resistance Gene Fhb7mentioning
confidence: 99%
“…ponticum . This strong FHB resistance QTL was pyramided into bread wheat (Shen and Ohm, 2007; Zhang et al, 2011; Forte et al, 2014) and also durum wheat (Forte et al, 2014) by exploiting the close relatedness of 7el 2 with 7el 1 (Dvorak, 1975; Guo et al, 2015a), deriving from a different accession of the same species. The latter bear genes for effective rust resistances ( Lr19 and Sr25 ) and for yield-contributing traits (see Ceoloni et al, 2015 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…ponticum chromosomes 7E1 and 7E2 in hybrids, with frequencies of meiotic pairing rates of 19.85 and 2.52, respectively ( 20 ). The genetic relationships based on molecular markers also revealed that 7E was distant from 7E1 and 7E2 ( 20 ). It was reported that resynthesized polyploids and natural polyploids have undergone many genetic changes, including sequence deletion, rDNA loci changes, transposon activation and chromosomal rearrangement ( 2127 ).…”
Section: Discussionmentioning
confidence: 99%
“…elongatum chromosome 7E paired occasionally with Th. ponticum chromosomes 7E1 and 7E2 in hybrids, with frequencies of meiotic pairing rates of 19.85 and 2.52, respectively ( 23 ). The genetic relationships based on molecular markers also revealed that 7E was distant from 7E1 and 7E2 ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation